A Versatile Chemoenzymatic Nanoreactor that Mimics NAD(P)H Oxidase for the In Situ Regeneration of Cofactors. (13th July 2022) - Rodriguez‐Abetxuko, Andoni; Reifs, Antonio; Sánchez‐deAlcázar, Daniel; Beloqui, Ana
Abstract: Herein, we report a multifunctional chemoenzymatic nanoreactor (NanoNOx) for the glucose‐controlled regeneration of natural and artificial nicotinamide cofactors. NanoNOx are built of glucose oxidase‐polymer hybrids that assemble in the presence of an organometallic catalyst: hemin. The design of the hybrid is optimized to increase the effectiveness and the directional channeling at low substrate concentration. Importantly, NanoNOx can be reutilized without affecting the catalytic properties, can show high stability in the presence of organic solvents, and can effectively oxidize assorted natural and artificial enzyme cofactors. Finally, the hybrid was successfully coupled with NADH‐dependent dehydrogenases in one‐pot reactions, using a strategy based on the sequential injection of a fuel, namely, glucose. Hence, this study describes the first example of a hybrid chemoenzymatic nanomaterial able to efficiently mimic NOx enzymes in cooperative one‐pot cascade reactions. Abstract : NanoNOx hybrids, consisting of glucose oxidase (GOx) enzymes individually wrapped by a catalytic polymer, were designed for the glucose‐mediated regeneration of nicotinamide cofactors. With this confined distribution, hydrogen peroxide generated in situ is injected into the organometallic catalyst, which is ultimately responsible for the oxidation of the cofactor. The system was successfully coupled to NAD‐dependent enzymes.